HORIZONTAL EQUITY, SELF-EFFICACY, AND BUDGETARY SLACK: COMPARING AMERICAN AND BRAZILIAN CULTURES - Robey, Shawn L.; McKnight, Mark A.; Thomas, Reshowrn B.; Mings, Amy L. (International Journal of Accounting & Finance Review, 2022)
This study analyzed the effect cross-cultural differences in perceived horizontal equity and self-efficacy have on the creation of budgetary slack.  This research addressed the gap in the role of ethical ideology in business by empirically examining the influence of culture on an individual’s ethical ideology and their propensity to create budgetary slack.  A total of 803 subjects included 413 individuals from America and 390 from Brazil.   A series of analysis of variance testing identified statistical significance between horizontal equity and the creation of budgetary slack, as well as statistically significant differences between low/high years of experience and budgetary slack levels.  Additional cross tabulations were included related to both horizontal equity as well as self-efficacy.  The results highlight budgetary procedures that may impact a person’s perceptions of fairness in pay compared to colleagues or peers with similar positions in organizations.  Findings suggest that employees with more years of professional experience could benefit from education on potential negative unintended consequences of creating slack in their budgetary decisions.  Our findings may be used by managers to gain awareness of this significance and take necessary steps to create equitable pay policies and budgetary targets. Study results indicated no statistical difference in slack levels between Americans and Brazilians.JEL Classification Codes: F39, G31, G41, M10, M49.